O Interdyscyplinarnym Centrum Badań Humanistycznych - Pietrych, Krystyna (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2025)
The text presents the Interdisciplinary Centre for Research in the Humanities of the University of Łódź formed in April 2014, its structure and scope of activity. The Centre has been established in order to initiate and coordinate the work of researchers representing different disciplines of the humanities and social science, such as philology, philosophy, anthropology, cultural studies, psychology, sociology, history and pedagogy. It has set itself two objectives: multidisciplinary research and projects on the humanities, and promoting humanistic attitudes in the modern world.